2022
DOI: 10.3389/fnhum.2021.765371
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Investigation of Brain MRI Lesions According to Whole Sample and Visual Function Subtyping in Children With Cerebral Visual Impairment

Abstract: Background: There is limited research on brain lesions in children with cerebral visual impairment (CVI) of heterogeneous etiologies and according to associated subtyping and vision dysfunctions. This study was part of a larger project establishing data-driven subtypes of childhood CVI according to visual dysfunctions. Currently there is no consensus in relation to assessment, diagnosis and classification of CVI and more information about brain lesions may be of potential diagnostic value.Aim: This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In this subtype we see reduced lower order visual defects with minimal or no VPDs probably as a result of retrograde degeneration of ganglion cells. In a follow up study Sakki et al (2022) compared their severity-based classification with MRI brain lesions and found no associations between visual function score and MRI lesions. However, another study showed a correlation between visual function score (without visual perception) and subcortical structures, corpus callosum, and cerebellum (Tinelli et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…In this subtype we see reduced lower order visual defects with minimal or no VPDs probably as a result of retrograde degeneration of ganglion cells. In a follow up study Sakki et al (2022) compared their severity-based classification with MRI brain lesions and found no associations between visual function score and MRI lesions. However, another study showed a correlation between visual function score (without visual perception) and subcortical structures, corpus callosum, and cerebellum (Tinelli et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Spearman's correlation coefficient (ρ) was used to indicate the relationship between the VFCS and the GMFCS, MACS, CFCS and EDACS. As CVI is affected by damage in the post‐geniculate visual pathways and visual cortex region (Sakki et al, 2021), the brain injury sites that affect VFCS and ‘GMFCS, MACS and EDACS’ are expected to differ. Therefore, we did not expect any strong correlation between VFCS and GMFCS, MACS, or EDACS.…”
Section: Methodsmentioning
confidence: 99%
“…About 60%-70% of children with CP are reported to have CVI (Schenk-Rootlieb et al, 1994;Uggetti et al, 1996), although a recent systematic review reported the presence of some ambiguities in the definition of CVI (Philip et al, 2020). In a recent review and study (Sakki et al, 2018(Sakki et al, , 2021, attempts have been made to define CVI subtype classifications.…”
Section: Introductionmentioning
confidence: 99%